Red flags for episiotomy in a midwife-led birth: using co-production with midwives to capture clinical experience - Maclellan, J; Gould, J; Webb, SS; Byrne, C; Brace, E; Glyn-Jones, E; Edwards, E; Hunter, T; Longton, J; Cleary, J; Christie, K; Dow, L (Elsevier, 2022)
Background: One of four key points in the Obstetric Anal Sphincter Injury Care Bundle, first piloted in the UK in 2016, was the directive to perform episiotomy when clinically indicated. Midwives are the primary health care professional for straightforward births in the UK and there is very little published literature that relates to their practice in this area.